Cardamonin attenuated thermal hyperalgesia in rheumatoid arthritis-induced rats : Possible involvement of TNF-a and IL-1ß suppression - Fui Ling, Voon; Ming Tatt, Lee; Ahmad Akira, Omar Farouk; Enoch Kumar, Perimal; Daud Ahmad, Israf; Mohd Roslan, Sulaiman (2016)
Rheumatoid arthritis (RA) is an autoimmune disease which causes chronic inflammation and pain on the systemic joints. The RA patients often suffer from painful joints especially when flares occur. Pro-inflammatory cytokines are the mediators that play a major role in inducing and maintaining the disease process in RA. Cytokines such as tumour necrosis factor- alpha (TNF-α) and interleukin-1 beta (IL-1ß) are abundantly expressed in RA. They contribute to pain indirectly through generation of inflammatory mediators which act on neurons by binding to highly expressed TNF-α and IL-1ß receptors. The aim of this study was to investigate the inhibitory effect of 2’,4’-dihydroxy-6’-methoxychalcone (cardamonin) on RA-induced thermal hyperalgesia and its possible target of pro-inflammatory cytokines. Rat model of rheumatoid arthritis were induced via intra-plantar (i.pl.) complete Freund’s adjuvant (CFA, 100µl) administration in the right hind paws. RA-induced rats were subjected to Hargreaves plantar test, in which the experimental rats were subjected to infrared heat source to RA-induced hind paw. The withdrawal latency of the paw was recorded as nociceptive response. Six groups of rats (n=6) were given cardamonin (0.625, 1.25, 2.5, and 5.0 mg/kg, i.p.), dexamethasone (3.0mg/kg, i.p.) and vehicle (10ml/kg, i.p.). At the end of the study, rat’s serum were collected and enzyme-linked immunosorbent assay (ELISA) was carried to assess the level of systemic TNF-α and IL-1ß. Cardamonin was shown to significantly increase the withdrawal response latencies in the thermal hyperalgesia in the RA rat paws while significantly decrease the systemic TNF-α and IL-1ß in the rats. The present result suggested that cardamonin reduced arthritic pain by suppressing TNF-α and IL-1ß level. This finding showed that cardamonin significantly reduced the nociceptive response in rheumatoid arthritis-induced rats, with possible involvement of TNF-α and IL-1ß suppression.